Gut Microbial Metabolites in Inflammatory, Metabolic, and Neurologic Disorders. - Atul Khajuria *1,; Ashish Kumar 2,; Prabhdeep Singh; Mahesh Gaba, (Emerging Trends in Metabolites, 2026)
The human gut microbiota transforms dietary and hostderived substrates into a diverse array of metabolites—including shortchain fatty acids (SCFAs), hydrogen sulfide (H₂S), bile acid derivatives, indoles, trimethylamine Noxide (TMAO), branchedchain amino acid (BCAA) derivatives, and lipopolysaccharide (LPS)—that act as key signaling mediators along epithelial, immune, endocrine, and neural axes. These metabolites regulate barrier integrity, energy homeostasis, inflammation, and gut–brain communication and are increasingly implicated in the pathogenesis of inflammatory bowel disease (IBD), obesity, type 2 diabetes, metabolic dysfunction–associated steatotic liver disease (MASLD), and central nervous system (CNS) disorders. SCFAs, particularly butyrate, support colonocyte metabolism, reinforce tight junctions, promote regulatory T cells, and modulate enteroendocrine hormone release, whereas dysbiosis-associated depletion of SCFA-producing taxa correlates with barrier failure and heightened inflammation in IBD, metabolic disease, and neuroinflammatory conditions. Microbiota-derived H₂S exhibits dose-dependent effects, contributing to mucosal defense at physiological levels but impairing butyrate oxidation, damaging the epithelium, and worsening metabolic control when produced in excess.Microbial conversion of primary to secondary bile acids shapes FXR/TGR5 signaling, lipid and glucose metabolism, innate immunity, and microbial ecology, while perturbations in bile acid pools are linked to MASLD, insulin resistance, and IBD. In the microbiota–gut–brain axis, SCFAs and tryptophan catabolites influence microglial maturation, neuroinflammation, and neuroplasticity, with reduced SCFA levels and altered indole profiles described in Parkinson’s disease, multiple sclerosis, and mood disorders. Emerging therapeutic strategies target these metabolite pathways using highfiber and prebiotic diets, SCFA- producing probiotics, fecal microbiota transplantation, bile acid receptor modulators, and approaches to modulate H₂S and other metabolites, though current human evidence is largely associative and heterogeneous. Future work integrating multi-omics with longitudinal and interventional designs, alongside efforts toward standardization and personalization, will be essential to establish causality and safely harness microbial metabolites as precision targets in inflammatory, metabolic, and neurologic disorders.
Keywords: Bile Acid Signaling; Keywords- Gut Microbiota Metabolites; Metabolic and Inflammatory Disorders; Microbiota–Gut–Brain Axis; Short-Chain Fatty Acids (SCFAs)